An Unusual Cause of Efferent Loop Obstruction (Journal of Enam Medical College, 2021)
Efferent loop obstruction is a very rare post-gastrectomy obstruction that can occur following Billroth-II or Roux-en-Y reconstruction. Here we report a case who underwent gastrojejunostomy for gastric outlet obstruction 30 years back and now developed efferent loop obstruction due to phytobezoar. The efferent loop obstruction was successfully resolved by laparotomy.J Enam Med Col 2020; 10(2): 118-121